2017
DOI: 10.1080/07315724.2016.1246989
|View full text |Cite
|
Sign up to set email alerts
|

Oral Adenosine-5′-triphosphate (ATP) Administration Increases Postexercise ATP Levels, Muscle Excitability, and Athletic Performance Following a Repeated Sprint Bout

Abstract: Objective: Oral adenosine-5 0 -triphosphate (ATP) administration has failed to increase plasma ATP levels; however, chronic supplementation with ATP has shown to increase power, strength, lean body mass, and blood flow in trained athletes. The purpose of this study was to investigate the effects of ATP supplementation on postexercise ATP levels and on muscle activation and excitability and power following a repeated sprint bout. Methods: In a double-blind, placebo-controlled, randomized design, 42 healthy male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…While intravenous administration of ATP is bioavailable [ 240 ], several studies have shown that oral ATP is not systematically bioavailable [ 241 ]. However, chronic supplementation with ATP increases the capacity to synthesize ATP within the erythrocytes without increasing resting concentrations in the plasma, thereby minimizing exercise-induced drops in ATP levels [ 242 ]. Oral ATP supplementation has demonstrated initial ergogenic properties, after a single dose, improving total weight lifted and total number of repetitions [ 243 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While intravenous administration of ATP is bioavailable [ 240 ], several studies have shown that oral ATP is not systematically bioavailable [ 241 ]. However, chronic supplementation with ATP increases the capacity to synthesize ATP within the erythrocytes without increasing resting concentrations in the plasma, thereby minimizing exercise-induced drops in ATP levels [ 242 ]. Oral ATP supplementation has demonstrated initial ergogenic properties, after a single dose, improving total weight lifted and total number of repetitions [ 243 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral ATP supplementation has demonstrated initial ergogenic properties, after a single dose, improving total weight lifted and total number of repetitions [ 243 ]. ATP may increase blood flow to the exercising muscle [ 244 ] and may reduce fatigue and increase peak power output during later bouts of repeated bouts exercise [ 242 ]. ATP may also support greater recovery and lean mass maintenance under high volume training [ 245 ], however, this has only been reported in one previous study.…”
Section: Introductionmentioning
confidence: 99%
“…Since deterioration of pulmonary, renal, and gastrointestinal epithelia are characteristics of COVID-19, we now suggest implementing trials of ATP supplementation designed to prevent organ failure in these patients. We previously conducted studies administering high-dose oral ATP to athletes and advanced cancer patients resulting in improved athletic performance and cancer patient survival [ 4 , 24 , 35 , 39 ]. This approach is uncomplicated and easily applied in the setting of SARS-CoV-2-infected individuals who are not yet in intensive care and has the potential to reduce rates of hospitalization and intubation.…”
mentioning
confidence: 99%
“…The investigation about the influence of ATP supplementation on exercise performance is widely explored in the literature, demonstrating ergogenic effects ( Freitas et al, 2017 ; Purpura et al, 2017 ; Wilson et al, 2013 ). Recently, our group investigated the acute influences of ATP supplementation on performance during resistance exercise (4 sets until muscular failure with 80% of one-repetition maximum in squat exercise) and physiological response in trained men.…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated the influence of oral adenosine-5’-triphosphate (ATP) supplementation on resistance exercise performance, demonstrating ergogenic effects ( Freitas et al, 2017 ; Purpura et al, 2017 ; Wilson et al, 2013 ). The great interest of ATP supplementation can be associated with physiological effects of extracellular ATP on skeletal muscle excitability and vascular tissue.…”
Section: Introductionmentioning
confidence: 99%